2014
DOI: 10.1007/s12010-014-1099-4
|View full text |Cite
|
Sign up to set email alerts
|

6,6′-Bieckol Isolated from Ecklonia cava Protects Oxidative Stress Through Inhibiting Expression of ROS and Proinflammatory Enzymes in High-Glucose-Induced Human Umbilical Vein Endothelial Cells

Abstract: Hyperglycemia-induced oxidative stress accelerates endothelial cell dysfunctions, which cause various complications of diabetes. The protective effects of 6,6'-bieckol (BEK), one of phlorotannin compound purified from Ecklonia cava against high-glucose-induced oxidative stress was investigated using human umbilical vein endothelial cells (HUVECs), which is susceptible to oxidative stress. High glucose (30 mM) treatment induced HUVECs' cell death, but BEK, at concentration 10 or 50 μg/ml, significantly inhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…COX2 and PGE2 are important mediators of inflammation in endothelial cells (Li and Shah 2004). Recent studies have shown that certain phytochemicals attenuate high-glucose-or cytokine-induced increases in COX2 and PGE2 levels in human umbilical vein endothelial cells (Abbasi et al 2014;Chao et al 2011;Park et al 2014;Sheu et al 2008). In the present study, CZE attenuated the dRib-induced production of the inflammatory mediators COX2 and PGE2.…”
Section: Resultssupporting
confidence: 60%
“…COX2 and PGE2 are important mediators of inflammation in endothelial cells (Li and Shah 2004). Recent studies have shown that certain phytochemicals attenuate high-glucose-or cytokine-induced increases in COX2 and PGE2 levels in human umbilical vein endothelial cells (Abbasi et al 2014;Chao et al 2011;Park et al 2014;Sheu et al 2008). In the present study, CZE attenuated the dRib-induced production of the inflammatory mediators COX2 and PGE2.…”
Section: Resultssupporting
confidence: 60%
“…Our recent study has demonstrated that the antisenescence effect of calcium-channel blockers in human endothelial cells is associated with increased eNOS activity [ 8 ], implying that eNOS activation is important in the regulation of the senescence program in endothelial cells by NO-mediated delay of cellular senescence [ 2 ]. The activity of eNOS is regulated by reciprocal phosphorylation of the activating site Ser-1177 and inhibiting site Thr-495, which affects NO bioavailability [ 33 ]. We found that both constant and intermittent glucose led to no changes in eNOS total expression, Ser-1177 eNOS phosphorylation, Thr-495 eNOS dephosphorylation, or NO release from control levels in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…The 6,6 -bieckol compound isolated from E. cava demonstrated an inhibition for the high-glucose-induced cytotoxicity in human umbilical vein endothelial cells (HUVECs) and insulinoma cells, showing it can be a potential therapeutic agent against the hyperglycemia-induced oxidative stress. This problem results in diabetic endothelial dysfunction [219,220].…”
Section: Phlorotanninsmentioning
confidence: 99%